(untitled) (World Science, 2021)
We have developed a method of preventing TIOL rotation by using a standard capsule ring. We examined 46 patients (59 eyes) who underwent phacoemulsification and implanted TIOL. Rotation of TIOL 6 months after surgery in the control group with 22 eyes (70.9%), in the main group - with 12 eyes (42.85%). In the main group in all cases, the deviation of the TIOL axis did not exceed 6 degrees. The proposed method of prevention of rotation of TIOL allows to increase the efficiency of phacoemulsification of cataracts.